Pengaruh Ongkos Kirim dan Harga terhadap Perilaku Konsumen Pengguna Grab di Kota Medan - Ratna Ashary; Bayu Teta (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the impact of shipping costs and prices on the behavior of consumers using Grab services in Medan City. The research employs a quantitative approach through a survey by distributing questionnaires to 99 respondents who have utilized Grab services (GrabFood or GrabExpress) in the last six months. Data analysis is conducted using validity, reliability, normality, multicollinearity, heteroscedasticity tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination (R²) with the assistance of SPSS version 25 software. The results indicate that shipping costs have a positive but insignificant effect on consumer behavior (sig. 0.172 > 0.05), while price has a positive and significant effect on consumer behavior (sig. 0.000 < 0.05). Simultaneously, both variables significantly influence consumer behavior with a significance value of 0.000 < 0.05. The coefficient of determination shows that 50.8% of consumer behavior is influenced by shipping costs and prices, while the remaining percentage is affected by other variables outside the model. Based on these findings, it is recommended that Grab maintain competitive pricing and continue to innovate its services to attract more consumers.